2022
DOI: 10.1136/bcr-2021-248636
|View full text |Cite
|
Sign up to set email alerts
|

Rare cause of left eye floaters and blurred vision in an immunocompromised patient: acute retinal necrosis (ARN)

Abstract: Acute retinal necrosis (ARN) is a clinical syndrome featuring severe vitritis and occlusive vasculitis characterised by full thickness necrotising retinitis. ARN is usually caused by an acute infection by either varicella zoster virus or herpes simplex virus, rarely cytomegalovirus (CMV). ARN often occurs in healthy adults; occasionally affecting immunocompromised patients with poor prognosis including significant visual loss and detachment of the atrophic retina regardless of antiviral treatment. We presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Although HCMV infection can occur in healthy individuals, it is uncommon to observe symptomatic infection in individuals without immune suppression [3,20]. HCMV retinitis is a clinical syndrome characterized by full-thickness necrotizing retinitis, which can result in profound vision loss, retinal detachment, and permanent vision loss [21]. The possible transmission paths of HCMV include blood, prenatal intrauterine infection, perinatal infection through breast milk or genital secretions, saliva, and sperm [22,23].…”
Section: Pathogenesis Of Hcmv Ocular Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although HCMV infection can occur in healthy individuals, it is uncommon to observe symptomatic infection in individuals without immune suppression [3,20]. HCMV retinitis is a clinical syndrome characterized by full-thickness necrotizing retinitis, which can result in profound vision loss, retinal detachment, and permanent vision loss [21]. The possible transmission paths of HCMV include blood, prenatal intrauterine infection, perinatal infection through breast milk or genital secretions, saliva, and sperm [22,23].…”
Section: Pathogenesis Of Hcmv Ocular Diseasesmentioning
confidence: 99%
“…The symptoms of acute retinal necrosis include redness, ocular pain, photophobia, floaters, and blurred vision [32]. These studies suggest that the challenges in diagnosis and therapeutic challenges primarily in the absence of guidelines or evidence-based literature to follow [21].…”
Section: Interventions Of Hcmv Ocular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Age is an important factor in predicting the visual prognosis, with older individuals (>80 years old) having a poorer prognosis compared to middle-aged patients [ 85 ]. The patient’s immune status should always be considered in ARN cases [ 86 ], especially in those who are immunosuppressed or immunocompromised (e.g., those undergoing biologic therapy), and a comprehensive ophthalmic assessment should be performed when visual loss is reported [ 87 89 ]. Although some studies have reported cases of ARN in patients with recent SARS-CoV-2 infection, further research is needed to establish a definite association [ 90 ].…”
Section: Introductionmentioning
confidence: 99%